Fenotipia e genotipia de Streptococcus equi isolados de equinos da região sul do Brasil - Kirinus, Jackeline Karsten (2010)
The phenotypic characteristics [morphology, biochemical fermentation, antimicrobial susceptibility, index of multiple resistances to antimicrobials (MAR), minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of benzilpenicilin] of 38 Streptococcus equi isolates were evaluated in this study. The phenotypic analyses demonstrated three colony patterns, three carbohydrate fermentation patterns and variation from 0 to 0.4 in the index of multiple resistances to antimicrobials. All the isolates of S. equi demonstrated sensitivity to penicillin, both by the disc diffusion method and microdilution method. The average MIC and MBC for benzilpenincillin were of 0,0095 μg/mL and 0.0267 μg/mL for S. equi subsp. equi and of 0.0128 μg/mL and 0.0380 μg/mL for S. equi subsp. zooepidemicus. The samples of S. equi differed in the values of MIC and MBC (p<0,05). The size of the penicillin inhibition halo demonstrated a relation with the MIC and MBC for S. equi subsp. equi, however for the samples of S. equi subsp. zooepidemicus this relation was only verified with the MBC. The MIC of benzilpenincillin of the samples isolated from the Central, Planalto and South regions of Rio Grande do Sul were statistically similar, although different from the Paraná state sample, suggesting the atypical character of this strain. All S. equi isolates are sensitive to penicillin and sulfazotrim, confirming these as antibiotics of choice for the treatment of infections caused by this agent in the clinical veterinary practice. Genotypic characteristics were also analyzed (hsp60 gene partial sequencing and analysis) in 20 isolates of Streptococcus equi from clinical samples of horses with strangles. The phylogenetic analysis showed a politomy among the isolates, suggesting that the hsp60 gene does not allow the differentiation between S. equi subspecies. New studies are suggested with expansion of territory sampled or even with the application of other markers, in order to clarify the evolutionary patterns not resolved and to confirm or not the real genetic differences between subspecies.